Use of ultra-violet micro-beam irradiation in a study of the embryonic development of Drosophila melanogaster - Hathaway, David S. (University of Edinburgh, 1960)
(1) The utility of ultra-violet micro-beam irradiation as an effective tool in the study of insect embryology has, been demonstrated. (2) Experimental verification of the postulated presumptive germ layers or the blastoderm of Prosophila melanogaster has been presented (Figure E, p. 58) . Particular organ development was traced, to various regions of the respective germ layers (Figure D, p. 47). (3) a. The precursive gamete cells of the adult reproductive organs are those pole cells carried, into the posterior midgut invagination during gastrulation. b. The mesodermal rudiment of the embryonic gonad is formed independently of these precursive gamete cells; it is derived from the posterior half of the midventral mesodermal invagination. c. The interbiastodermal migrating pole cells do not become incorporated into the embryonic gonad as gamete precursors. Instead, they probably assume a role in the formation of midgut epithelium. (4) The condition of the adult reproductive organ of pole cell irradiated embryos varies and appears to be at least partially dependent upon the stage of development at which they are irradiated. Both bilateral and unilateral defects were observed in these adults, but only those embryos treated at the blastema stage were of only one kind, i.e.,bilateral. (5) Detailed information was obtained regarding the morphogenetic factors of the endodermal invagination (see ’’Discussion”). (6) Corroborative evidence was found for the presence of a "differentiation centre" in the presumptive thorax region of the blastema and blastoderm, although it was not possible to gain further information about its functional character. (7) The embryos exhibited, a much greater susceptibility to ulbra-violet damage at the blastema stage than at the blastoderm stage. This apparently is related to the incomplete cellular formation found in the blastema. (8) Gastrulation was a critical period in the development of irradiated embryos. The fault in morphogenesis was easily traced to the irradiation damage and that particular role in gastrulation which the damaged cells would normally assume.
The use of ultra-violet micro-beam irradiation in a study of the embryonic development of Drosophila melanogaster